Majelis Ta'lim: A Model of Non-Formal Islamic Education and Development (A Phenomenological Study of its Role, Opportunities and Challenges in the Modern Era) - M Fadli (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
Majelis ta'lim is a non-formal institution that plays a role in fostering and providing religious education to its congregation. In the past, majelis ta'lim was carried out traditionally, but with the rise of digitalization, the traditional forum was eroded by the modern majelis ta'lim model. The purpose of this research is to analyze the role, opportunities, and challenges of majelis ta'lim in today's modern era. This paper is produced from a literature review with a data collection model in the form of documentation from the web or virtual majelis ta'lim sites spread across various online media. In addition, this paper will also use important research results related to the issues discussed in this paper. The argument built from the results of this research is that the modern era of majelis ta'lim is very instrumental in the current pattern of Islamic education. Especially for Ustadz who is viral with various interesting studies. This is a great opportunity for Ustadz in packaging material to be delivered easily without requiring a large place like traditional ta'lim assemblies. However, behind this convenience, big challenges also arise. The challenge is related to the material of the taklim assemblies that feature different studies that cause people to become confused and allow misunderstanding of the material presented. The results of this study are expected to be new information in the model of guidance and education of majelis ta'lim.